Studies on the Removal of Red Industrial Dye Using Teak Leaf, Maize Corn and Babool Tree Bark Carbons -A Comparison - N. Kannan; A. Vijayakumar; P. Subramaniam (E-Journal of Chemistry)
Activated carbons prepared from teak leaf (TLC), maize corn (MCC) and babool tree bark (BTBC) were used to study adsorption of red industrial dye under various experimental conditions. Effect of various experimental parameters such as initial concentration, adsorbent dosage, particle size, contact time and initial pH of solution was studied. Batch adsorption studies were carried out at room temperature (30±1°C). Adsorption parameters were modeled by Freundlich and Langmuir isotherm models. Adsorption data were fitted with the Natarajan and Khalaf, Lagergren and Bhattacharya -Venkobachar equations. The high value of 21.28 was obtained from Langmuir plot indicates maize corn carbon (MCC) is the best low cost adsorbent. The adsorption process followed first order kinetics, with intra- particle diffusion as one of the rate limiting steps